2012
DOI: 10.7732/kjpr.2012.25.6.762
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Genetic Diversity and Fatty acid Composition of Perilla (Perilla frutescens var. frutescens) Germplasm

Abstract: -The objective of this study was to analyze the genetic diversity using SSR marker and investigate the fatty acid composition of perilla (P. frutescens var. frutescens) germplasm. Genetic diversity among 95 accessions, which consisted of 29 weedy types and 66 landrace accessions, was evaluated based on 12 SSR markers carrying 91 alleles. The mean values of observed (HO) and expected heterozygosities (HE) were 0.574 and 0.640, respectively, indicating a considerable amount of polymorphism within this collection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
2
2
0
Order By: Relevance
“…This variation could have happened due to regional barriers, heterosis, and/or man made selection (Upadhyaya et al, 2008). Present research also exhibited a higher PIC (0.518) than that reported earlier in foxtail millet (0.381) and rice (0.42) (Jin et al, 2010;Lin et al, 2012), but lower than that reported in maize (0.72), pearl millet (0.58), persimmon (0.67) and perilla (0.59) (Pejic et al, 1998;Kapila et al, 2007;Seo et al, 2013;Song et al, 2012). Here, we have used a combination of di-and trinucleotides that might be the cause of variation, because a higher number of dinucleotide repeats instead of trinucleotides or higher numbers increase the genetic variability (Yang et al, 2010).…”
Section: Discussionsupporting
confidence: 44%
“…This variation could have happened due to regional barriers, heterosis, and/or man made selection (Upadhyaya et al, 2008). Present research also exhibited a higher PIC (0.518) than that reported earlier in foxtail millet (0.381) and rice (0.42) (Jin et al, 2010;Lin et al, 2012), but lower than that reported in maize (0.72), pearl millet (0.58), persimmon (0.67) and perilla (0.59) (Pejic et al, 1998;Kapila et al, 2007;Seo et al, 2013;Song et al, 2012). Here, we have used a combination of di-and trinucleotides that might be the cause of variation, because a higher number of dinucleotide repeats instead of trinucleotides or higher numbers increase the genetic variability (Yang et al, 2010).…”
Section: Discussionsupporting
confidence: 44%
“…Meanwhile, the IT117093, IT117133, and IT157549 accessions showed the lowest total fatty acid content compared with the other accessions with a content of 97.3% or less ( Table 1 ). Most of the five fatty acid composition values investigated in this study were similar to those reported in previous studies on Perilla seeds [ 8 , 9 , 12 , 41 , 42 , 43 , 44 ]. However, the contents of the five fatty acids measured in each Perilla accession tended to be high or low, depending on the Perilla accession.…”
Section: Discussionsupporting
confidence: 90%
“…They are a good source of polyunsaturated fatty acids, such as linoleic acid and α-linolenic acid, as these account for about 80% of Perilla seed oil. In particular, two essential fatty acids, oleic and linolenic acid, are significant fatty acids in terms of quality and quantity of Perilla seed oils [ 11 , 12 , 13 , 41 ]. In addition, Perilla leaves are rich in vitamins B and C and are preferred as salad vegetables and pickles in South Korea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation